Quantum tunneling fragmentation model - Stošić, Borko D.; Gomes, M. A F; Adhikari, Sadhan K. [UNESP] (My University, 2000)
A nonthermal quantum mechanical statistical fragmentation model based on tunneling of particles through potential barriers is studied in compact two- and three-dimensional systems. It is shown that this fragmentation dynamics gives origin to several static and dynamic scaling relations. The critical exponents are found and compared with those obtained in classical statistical models of fragmentation of general interest, in particular with thermal fragmentation involving classical processes over potential barriers. Besides its general theoretical interest, the fragmentation dynamics discussed here is complementary to classical fragmentation dynamics of interest in chemical kinetics and can be useful in the study of a number of other dynamic processes such as nuclear fragmentation. ©2000 The American Physical Society.
Keywords: Charged particles; Computer simulation; Mathematical models; Monte Carlo methods; Reaction kinetics; Statistical mechanics; Temperature; Three dimensional; Two dimensional; Fragmentation dynamics; Nuclear fragmentation; Quantum mechanical statistical fragmentation model; Quantum tunneling fragmentation model; Thermal fragmentation; Quantum theory